2022
DOI: 10.7759/cureus.28987
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Correlates of Food Insecurity in Students Attending a Private University: A Cross-Sectional, Descriptive Study

Abstract: Background: Food insecurity is thought to be a prevalent yet misunderstood problem among college/university students. There is limited evidence regarding the prevalence of food insecurity in this population, and even less among private institutions of higher education. Food insecurity in college/university students can have harmful effects on students' academic performance and health. The aim of this study was thus to examine food security among college/university students and assess variables which may be ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…The same study also reported that the rate of food insecurity among international students during the same period increased from 29.89% to 40.8%, making them the most food insecure group in the study (Glantsman et al, 2022). Another study done at Nova Southeastern University, a large, private, suburban university in Florida found that out of the 744 graduate and professional students surveyed, 34.5% of them were food insecure (Lankford et al, 2022). These studies demonstrate how vulnerable the graduate student population is when it comes to food insecurity.…”
Section: Food Insecurity In Graduate Studentsmentioning
confidence: 79%
“…The same study also reported that the rate of food insecurity among international students during the same period increased from 29.89% to 40.8%, making them the most food insecure group in the study (Glantsman et al, 2022). Another study done at Nova Southeastern University, a large, private, suburban university in Florida found that out of the 744 graduate and professional students surveyed, 34.5% of them were food insecure (Lankford et al, 2022). These studies demonstrate how vulnerable the graduate student population is when it comes to food insecurity.…”
Section: Food Insecurity In Graduate Studentsmentioning
confidence: 79%